An Empirical Study of Internet-Based ICT Adoption Among Malaysian SMEs - Khong Sin, Tan; Uchenna Cyril, Eze (2008)
Small and Medium Enterprises (SMEs) are key economic sector in Malaysia and the Malaysian government have over the past decades promoted development and growth initiatives such as ICT implementation to advance their overall economic agenda. This paper, therefore, examines the factors and adoption patterns of Internet-based Information and Communication Technologies (ICTs) among SMEs in Malaysia. The Diffusion of Innovation underpins the conceptual framework in this paper. Questionnaire-based survey was used to collect data from 406 managers/owners of SMEs in the southern region of Malaysia. Data analysis indicates that Internet-based ICTs adoption among SMEs provides new business opportunities and access to market information and knowledge. Security and high ICT cost continues to be barriers to Internet-based ICTs adoption. Inferential analyses reveal that relative advantage, compatibility, complexity, observability and security are significant factors that influence Internet-based ICT adoption. The findings are discussed and interpreted to provide key implications to SMEs and Malaysian government.